2003
DOI: 10.1021/bi0273664
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evolution of the Binding Specificity of Neocarzinostatin, an Enediyne-Binding Chromoprotein

Abstract: Neocarzinostatin is the most studied member of the enediyne-chromoprotein family, and is clinically used as an antitumoral agent. Neocarzinostatin could be a promising drug delivery vehicle if new binding specificities could be conferred to its protein scaffold. We used in vitro evolution methods to demonstrate that this approach is feasible. We created large libraries containing between 1.7 x 10(8) and 1.4 x 10(9) independent clones, where up to 13 side chains pointing toward the binding crevice were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 26 publications
0
56
0
Order By: Relevance
“…stabilizing the bound drug and releasing the same by operating the side chain of a critical amino acid. apoNCS and its evolution variants are able to carry a number of small molecules such as ethidium bromide (50), nitrogen mustard (51), or testosterone (52). Taking into account of the enhanced DNA cleavage by Phe 78 mutants, the present drug release model provides a promising indication for engineering pharmacological packages in a broad functional context.…”
Section: Discussionmentioning
confidence: 99%
“…stabilizing the bound drug and releasing the same by operating the side chain of a critical amino acid. apoNCS and its evolution variants are able to carry a number of small molecules such as ethidium bromide (50), nitrogen mustard (51), or testosterone (52). Taking into account of the enhanced DNA cleavage by Phe 78 mutants, the present drug release model provides a promising indication for engineering pharmacological packages in a broad functional context.…”
Section: Discussionmentioning
confidence: 99%
“…However, holo-NCS is very unstable under the condition because of the free chromophore and we could not yet find a suitable condition for structure determination and relaxation studies. A possible alternative will be the investigation of the chromophore mimic compound complex with apo-NCS (11)(12)(13) in the dissociative condition with a combination of a static/dynamic structure comparison with holo-NCS. Our findings predict that an introduction of the aminosugar in the mimic compound significantly increases the binding affinity to allow the investigation under the dissociative condition.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms were dominated by hydrophobic interactions with the binding pocket. However, the mechanism of releasing and binding of the chromophore remains unclear, even though the process has attracted much attention and has been investigated by a variety of methods (8,11,22,23). In the previous NMR structure ensemble, the loop structures have particularly poor convergence and this was assumed to be caused by structural flexibilities, which were thought to be responsible for the chromophore-releasing mechanism (15,17,18).…”
mentioning
confidence: 99%
“…9) Nicaise et al reported the affinity transfer from antibody to apo-NCS by the CDR3 grafting of the VHH chain of camel anti-lysozyme antibody. Thus, apo-NCS randomized library would be one of most promising resource for newly caged protein.…”
Section: Discussionmentioning
confidence: 99%